The implications of social distancing due to COVID-19 on the mental health of children and adolescents in Guanambi – BA (Research, Society and Development, 2024)
Introduction: Measures such as social isolation had to be adopted during the COVID-19 pandemic, where children and teenagers were removed from their activities and social life, bringing neuropsychological impact. Objective: To assess the implications caused by social distancing by COVID-19 on the mental health of children and adolescents in a Basic Health Unit (UBS) in the municipality of Guanambi - BA, Brazil. Methods: This is cross-sectional research, with a quantitative and descriptive approach, through field research in which children and adolescents from 4 to 18 years old were evaluated, all users of a UBS, located in a city in the interior of Bahia. Data were collected through the application of a questionnaire with the parents of children and adolescents.  Data analysis were made with the help of the Statistical Package for the Social Sciences (SPSS)® version 20 to perform descriptive statistics and bivariate analyses. Results: The data analyzed showed that parents got a perception regarding the changes in the emotional state of children and adolescents during the period of social isolation, especially for those who had COVID-19 and those who did not have an outside space in their homes to play. Conclusion: The pandemic had a negative impact on the mental health of children and adolescents, leaving this group more vulnerable to anxiety, stress, depressive symptoms, mainly due to isolation and the affected socioeconomic conditions. Greater attention to mental health care for individuals in this age group is necessary.